Counteracting Globalization's Skeptics: How Diasporas Influence the Internationalization Preferences of Minority Entrepreneurs' Firms - Inouye,Todd M; Joshi,Amol; Hemmatian,Iman; Robinson,Jeffrey A (Global Strategy Journal, 2019)
Keywords: Strategy & Entrepreneurship

Does a Federal Glass Ceiling Have Differential Effects on Female and Male Technology Entrepreneurs? - Inouye,Todd M.; Robinson,Jeffrey A.; Joshi,Amol (2019)
Keywords: Strategy & Entrepreneurship

Urban Innovation: At the nexus of entrepreneurship and urban policy - Robinson,Jeffrey A; Joshi,Amol; Vickerie-Dearman,Lutisha; Inouye,Todd M (2019)
We define urban innovation as the development of long-lasting transformations in urban communities, neighborhoods, and cities. In our proposed framework, urban innovation is driven by two overarching principles: social inclusion and transformation. Inclusion allows for interaction across social groups and benefits society by reducing socio-economic separation through fostering stronger, and even new, relationships in the community. Transformation means deep-seated change that remodels the mindset and creates new change agents. These principles enable us to isolate innovative activities that are small and incremental, from urban innovations that have the potential to impact the economy and society in major ways. We identify three distinct types of transformative and inclusive policy innovations used in the urban innovation context: market creating, market integration, and market incentivizing. We also present three types of business model innovations that work within these innovations: social entrepreneurship, technology and innovation parks, and venture accelerators. We further categorize the social entrepreneurship business model into sustainable or triple bottom line businesses, social enterprises, micro-finance organizations and benefits corporations/B-Corps. We highlight specific examples of these policy and business model innovations from around the world to illustrate how and why urban innovations are essential for economic growth and social development in rapidly urbanizing cities. We also present several promising avenues for new research on urban innovation to guide scholars, practitioners, and policymakers in more systematically studying the phenomenon and in making strategic decisions about critical issues related to future of the world’s cities.
Keywords: Strategy & Entrepreneurship

Content, Contribution, and Knowledge Consumption: Uncovering Hidden Topic Structure and Rhetorical Signals in Scientific Texts - Antons,David; Joshi,Amol; Salge,Torsten Oliver (Journal of Management, 2018)
Knowledge production and scientific discourse are observable in published scholarly texts. Citations capture knowledge consumption and impact. Drawing from the sociology of science, our theoretical framework posits scientific communities as thought collectives with distinctive thought styles that embed a hidden topic structure and rhetorical signals into a journal’s published articles. We hypothesize and uncover how an article’s topic attributes (structure, focus, and newness) and rhetorical attributes (inclusiveness, exclusiveness, tentativeness, and certainty) indicate future knowledge consumption. We empirically test our ideas by applying text mining algorithms to model topics and extract rhetorical signals from 1,646 strategy articles composed of nearly 18 million words generating 172,237 citations over 35 years. We find that strategy articles’ hidden topic structure explains 14% of variance in scientific impact. We also show that topic focus and topic newness each independently, directly, and significantly increase impact. As for newness, the first two articles published on a new topic each generate a citation premium of more than 100%, which is higher within the focal thought collective than outside. Importantly, we uncover that the citation premium of newness increases with greater topic focus, which attracts attention, and greater inflow of prior intra-collective knowledge, which enhances absorption. Impact also increases when authors present new topics using a rhetorical style that is more tentative than certain. Overall, our findings demonstrate that topic and rhetorical attributes as constitutive elements of scientific content are independently and interdependently related to the consumption of strategy research across thought collectives in management research.
Keywords: Strategy & Entrepreneurship

How do legal surprises drive organizational attention and case resolution? An analysis of false patent marking lawsuits - Joshi,Amol; Hemmatian,Iman (Research Policy, 2018)
Legal surprises are unexpected suits or actions in which plaintiffs rely on claims or precedents that may be obscure, unfamiliar, or unknown to the defendants. Our study explores false patent marking suits, a unique type of patent-related legal surprise involving allegations of defendants marking products with ineligible patent numbers to deceive customers and/or deter competitors. An abrupt shift in U.S. Federal Courts’ interpretation of intellectual property rights (IPRs) policy amplified plaintiff incentives for filing these suits while escalating defendant penalties for proven violations. Handling costly legal surprises such as false patent marking suits requires focused attention from managers. Our core premise is that temporal and evidential cues in the timelines and storylines of plaintiffs’ legal narratives in surprise suits attract defendants’ organizational attention. We hypothesize about temporal focus (past, present, and future) and evidentiary reasoning (relevance, credibility, and inferential power) as attention cues and possible predictors of the mode (litigation or negotiation) and timing of case resolution. We apply automated content analysis to official court records for 992 false patent marking cases (2009-2011) and quantify competing risks using hazard models. We find that differences in temporal focus and evidentiary reasoning in the legal narratives of surprise suits are significant predictors of case resolution mode and timing. We also find that defendants countersuing to redirect plaintiffs’ attention is an effective negotiating tactic. We discuss the economic significance and strategic implications of our empirical findings on legal surprises, attention, case resolution mode and timing, and the unintended consequences of IPR policy changes.
Keywords: Strategy & Entrepreneurship

Glass Ceiling Effects for Minority and Women Technology Entrepreneurs - Joshi,Amol; Inouye,Todd M; Robinson,Jeffrey A (Rutgers Advanced Institute for the Study of Entrepreneurship and Development (RAISED), 2017)
Keywords: Strategy & Entrepreneurship

How does agency workforce diversity influence Federal R&D funding of minority and women technology entrepreneurs? An analysis of the SBIR and STTR programs, 20012011 - Joshi,Amol; Inouye,Todd M; Robinson,Jeffrey A (Small Business Economics, 2017)
U.S. Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs provide Federal research and development (R&D) grants to technology ventures. We explore how grantor demographic diversity explains why demographically diverse grantees experience different odds for successfully transitioning from initial to follow-on R&D grants. We empirically analyze 52,126 Phase I SBIR/STTR awards granted by 11 Federal agencies (2001-2011). We find a positive association between agency workforce diversity and Phase II funding for Phase I grantees, but minority and women technology entrepreneurs are less likely to receive this funding than their non-minority and male counterparts. Agencies valuing workforce ethnic diversity or leveraging gender homophily positively influence the likelihood of women technology entrepreneurs obtaining Phase II funding. We discuss evidence-based implications for policy and practice.
Keywords: Strategy & Entrepreneurship

The Impact of Bankruptcy on Competitors: How Technology Overlap and Diversification Affect Value Redistribution. - Arthurs,Jonathan; Cho,Sam Yul; Choi,Yohan; Hemmatian,Iman; Joshi,Amol (AOM 2017 Annual Meeting, 2017)
Keywords: Strategy & Entrepreneurship

Impact of Bankruptcy on Rivals: How Tech Overlap and Diversification Affects Value Redistribution - Arthurs,Jonathan; Cho,Sam Yul; Choi,Yohan; Hemmatian,Iman; Joshi,Amol (Academy of Management Proceedings, 2017)
Prior research on bankruptcy proposes two potential outcomes for a bankrupt firm’s industry rivals: a contagion effect wherein rivals’ stock prices decline, and a competitive effect wherein rivals benefit from a competitor’s decline. Although empirical evidence substantiates the contagion effect, existing studies do not consistently account for the competitive effect. We develop and test theory explaining how the degree of technology overlap and diversification strategy of competitors influences the severity of the contagion effect and the expected occurrence of the competitive effect among rivals. We find that greater technology overlap among a bankrupt firm and its competitors exacerbates the contagion effect. Furthermore, competitors with higher unrelated diversification are more susceptible to contagion, while competitors with higher related diversification benefit more from a rival’s bankruptcy.
Keywords: Strategy & Entrepreneurship

Innovation Policy - Joshi,Amol (2014)
This entry outlines the concept of innovation policy in the domain of strategic management. First, an overview of the history, goals and underlying principles of innovation policy is presented. Next, the primary functions and possible means of implementing innovation policy are described with an emphasis on theoretical foundations. Finally, the evaluation of innovation policy outcomes, including the intended and unintended consequences of policy changes, are briefly discussed.
Keywords: Strategy & Entrepreneurship

Language friction and partner selection in cross-border R&D alliance formation - Joshi,Amol; Lahiri,Nandini (Journal of International Business Studies, 2014)
How does language friction affect alliance formation? Language friction is a form of cultural friction arising from structural differences in the respective languages used by potential partners to reason and solve problems together. A little language friction may prompt partners to rethink solutions, thereby enhancing collaboration, but excessive friction may impede collaboration. We develop a Language Friction Index (LFI) to quantify relative differences in linguistic structure for any language pair. Utilizing a unique data set of semiconductor design activities (1988–2001), our empirical analysis finds an inverted U-shaped relationship between partners’ LFI and the likelihood of cross-border research and development (R&D) alliance formation. This relationship is further moderated by prior ties and technological distance. Our findings have several important implications, including: (1) language differences are a measurable and discernible source of cultural friction; (2) the effects of language friction are economically significant and strategically consequential; (3) certain aspects of language friction occur independent of language proficiency and persist despite the use of lingua franca to reduce language barriers; (4) linguistic diversity is an indirect marker of cognitive diversity, which is useful in boosting creativity, especially in first-time collaborations; (5) beyond R&D alliances, language friction may also influence other types of strategic interactions and organizational processes.
Keywords: Strategy & Entrepreneurship

The Power of Words: How, Why, and When Do Language Barriers Affect Alliance Formation?" - Joshi,Amol; Lahiri,Nandini (Academy of Management Proceedings, 2014)
We extend previous research on language issues within firms by examining the strategic consequences of language barriers between firms. We elaborate underlying mechanisms of how, why, and when language differences matter in the selection of cross- border R&D partners. We develop a language distance construct which captures relative differences in linguistic structure for any language pair. We hypothesize and find situations in which language differences help, rather than hinder alliance formation. Our empirical results suggest an inverted U-shaped relationship between language distance and the likelihood of alliance formation. This relationship is further moderated by potential partners’ prior ties and technological distance.
Keywords: Strategy & Entrepreneurship

Which Technologies are Included in Patent Pools? How Market and Social Factors Impact Selection - Joshi,Amol; Nerkar,Atul; Mallapragada,Girish (Academy of Management Proceedings, 2014)
Patent pools are a unique form of research and development (R&D) consortium in which licensor firms (technology sellers) bundle together essential patents for licensing out to each other and to third-party licensee firms (technology buyers). Over the last hundred years, governments rarely approved patent pools because of concerns about excessive or inappropriate knowledge sharing among participating firms and the possibility of anti-competitive activity. However, in recent years, regulatory authorities in the United States and Europe enacted policy changes and sanctioned the formation of patent pools in a variety of industries that are economically and technologically important. In this study, we utilize the formation of patent pools as a natural experiment for testing a much debated proposition in organizational research ––– market-based versus network- based explanations for technology selection by firms. For the patents which technology sellers seek to license out to technology buyers, we posit that both the market value of the invention and the network position of the inventor impact the selection of patents for bundling in a patent pool. We conduct empirical analyses utilizing data from multiple patent pools formed within the same timeframe and within the same industry (optical discs). We find that market and network factors reinforce, rather than counteract each other in driving which patents are deemed essential and bundled together in a pool. Our findings have strategic implications for firm-level innovation by technology sellers and buyers as well as policy implications for government regulators.
Keywords: Strategy & Entrepreneurship

When Are Patent Litigants Productive or Unproductive Entrepreneurs? Evidence from a Natural Experiment on False Patent Marking, 2007-2011 - Joshi,Amol (2013 SMS Conference, 2013)
Keywords: Strategy & Entrepreneurship

Do Dealmakers Make a Difference? Evidence from the Social Capital Networks of Serial Entrepreneurs and Investors - Zoller,Ted; Joshi,Amol; Ethridge,Frank (2012 SMS Conference, 2012)
Keywords: Strategy & Entrepreneurship

Information Asymmetry and Partner Selection in International Alliances - Joshi,Amol; Lahiri,Nandini (Academy of Management Proceedings, 2012)
We extend prior research on intra-firm language barriers by investigating inter-firm language barriers in cross-border alliances. Integrating concepts from sociolinguistics and information economics, we posit that language barriers between potential partners exacerbate information asymmetries, while market signals of the commercial value of a partner’s knowledge counteract these asymmetries. To test these ideas, we quantify language barriers using a distance measure of linguistic differences and we analyze data on semiconductor alliances during 1988-2001. Controlling for cultural, geographical, and technological distances, our empirical results suggest that firms overcome large language distances by relying on market signals of a prospective partner's level of disclosure, stock of knowledge, and degree of specialization. Stronger signals significantly dampen the negative impact of language distance on the chances of forming an alliance.
Keywords: Strategy & Entrepreneurship

Stocking the Patent Pool: What Do Firms Offer for Licensing and Why? - Joshi,Amol; Nerkar,Atul; Mallapragada,Girish (Academy of Management Proceedings, 2012)
Licensing out intellectual property (IP) such as patents is an important source of firm profit. However, the managerial logic for determining which IP firms offer for licensing remains underexplored in the management literature. Past research analyzes the downstream purchasing decisions of IP licensees. In contrast, this study uses the concept of patent pools, a type of R&D consortium, to explore the upstream marketing decisions of IP licensors. Drawing on the resource-based view (RBV), we hypothesize and find that an increase in the value of IP significantly increases the likelihood that the IP is offered for licensing through a patent pool, while an increase in the imitability of IP significantly decreases the likelihood that the IP is offered for licensing. Further, we find differential effects for the intrinsic and extrinsic dimensions of value and imitability on the likelihood of IP licensing. Extrinsic imitability of IP negatively moderates the relationship between the value of IP and the likelihood it is offered for licensing through a pool, whereas intrinsic imitability positively moderates this relationship. Our findings extend the RBV by providing empirical evidence for how managers determine and use the value and imitability of a firm’s IP portfolio to justify technology licensing decisions.
Keywords: Strategy & Entrepreneurship

When do strategic alliances inhibit innovation by firms? Evidence from patent pools in the global optical disc industry - Joshi,Amol; Nerkar,Atul (Strategic Management Journal, 2011)
Research and development (R&D) consortia are specialized strategic alliances that shape the direction and scope of firm innovation activities. Little research exists on the performance consequences of participating in R&D consortia. We study the effect of patent pools, a unique form of R&D consortia, on firm performance in innovation. While prior research on alliances generally implies that patent pools enhance firm innovation, our study finds the opposite. Analyzing data on systemic innovation in the global optical disc industry, we find that patent pool formation substantially and significantly decreases both the quantity and quality of patents subsequently generated by licensors and licensees relative to the patenting activity of nonparticipants. Our empirical findings suggest that patent pools actually inhibit, rather than enhance, systemic innovation by participating firms.
Keywords: Strategy & Entrepreneurship